Molecular simulation studies and systems biological approach to identify the target lead compound for the enzyme DNA gyrase - Rajakumari Karuppaiah, Brindha Devi Parthiban, Shanmugapriya Rishikesan, Balamugundan Munusamy, Aravind Kaliyamurthy, Sundar Himalanathan (Journal of Applied Pharmaceutical Science, 2025)
In view of the emergence of resistance to antibiotics, Staphylococcus aureus is currently a major threat to world health. An interesting alternative for treating staphylococcal infections is herbal therapy. Our research focuses on the possibility of finding new treatments that can be used to create cutting-edge therapies from medicinal plants. Gene-encoding protein networks have been investigated using systems biology. Bioactive compounds derived from Vitex negundo, Euphorbia hirta, and Solanum nigrum were molecularly docked against the protein with PDB ID: 5D7D. In the evaluation of pharmacological target characteristics using molecular dynamics simulations in NAMD software for 100 ns, a promising bioactive molecule with high binding energy was identified. These promising results indicate the potential for effective treatment of staphylococcal infections with metabolites produced from medicinal plants. The target of the DNA gyrB gene, which plays a role in bacterial supercoiling, is effective at preventing infections from spreading. The research presented here enhances our understanding of molecular pathways and recommends lead 1 (Bicyclo [7.2.0] Undec-4-Ene,4,11,11-Trimethyl-8-Methylene-, [1r-(1r*,4z,9s*)]-) as a prospective therapeutic target. The insights highlighted the potential for the progress of regulatory standards and the creation of effective medications through computational research.
Keywords: Staphylococcus aureus, medicinal plants, cytoscape, molecular docking, molecular simulations